Predicting Intention to Use Shopee PayLater Among Accounting Students: A Technology Acceptance Model (TAM) Approach - Febriana; Masruddin; Fikry Karim; Rahayu Indriasari (GoodWill, 2024)
This study aims to determine the effect of usefulness and convenience on the interest of Tadulako University students in using Shopee Paylater. This research is descriptive verification research. The questionnaire was distributed to 96 accounting students at Tadulako University. The analysis method used is multiple linear regression analysis. The results concluded that usefulness and convenience have a positive and significant effect on the interest of Tadulako University students in using Shopee Paylater. Usefulness have a positive and significant effect on the interest of Tadulako University students in using Shopee Paylater. Convenience has a positive and significant effect on the interest of Tadulako University students in using Shopee Paylater. The research findings have implications for the real practice of using shopee paylater not only among accounting students but also to a wide audience. Further research is suggested to be able to examine more deeply the perspective of convenience and usefulness can be applied to the use of other payment media in real daily practice.